THE INTERNATIONAL PRACTICE OF GLOBALIZATION IN HEALTH SYSTEM - V. A. Alekseev; K. N. Borisov (Модернизация, инновация, развитие, 2015)
The social aspect of globalization is characteristic that in health care the increasing distribution is received by market mechanisms, turning medical care into the goods in «the market trading in services». In the conditions of inevitability of globalization experts of WHO recommend to observe a uniform world trend in health care availability, justice, quality of medical care. It often not productively as the same experts of WHO ascertain. In most cases, unfortunately, the effect appears negative. The general in health care reforming in the modern world of globalization is the state way of financing and health care regulation, including obligatory medical insurance (compulsory health insurance) and the state guarantees of free medical care with emphasis on prevention.